Stabilization of the dual-aromatic cyclo-N5− anion by acidic entrapment - Zhang, Lei (2020)
Pentazole anion, the best candidate for full-nitrogen energetic materials, can be isolated only from acidic solution for unclear reasons, which hinders the high-yield realization of a full-nitrogen substance with higher energy density. Herein, we report for the first time the discovery of the dual aromaticity (π and σ) of cyclo-N5–, which makes the anion unstable in nature but confers additional stability in acidic surroundings. In addition to the usual π-aromaticity, similar to that of the prototypical benzene, five lone pairs are delocalized in the equatorial plane of cyclo-N5–, forming additional σ-aromaticity. It is the compatible coexistence of the inter-lone-pair repulsion and inter-lone-pair attraction within the σ-aromatic system that makes the naked cyclo-N5– highly reactive to electrophiles and easily broken. Only in sufficiently acid solution can the cyclo-N5– become unsusceptible to the electrophilic attack and gain extra stability through the formation of hydrogen-bonded complex from surrounding electrophiles; otherwise, the cyclo-N5– cannot be productively isolated. The dual aromaticity discovered in cyclo-N5– is expected to be universal for pnictogen five-membered ring systems.